2004
DOI: 10.1097/01.olq.0000137904.56037.70
|View full text |Cite
|
Sign up to set email alerts
|

Hormonal Contraceptive Use, Cervical Ectopy, and the Acquisition of Cervical Infections

Abstract: DMPA use, but not OC use, appeared to be significantly associated with increased acquisition of cervical chlamydial and gonococcal infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
71
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(75 citation statements)
references
References 26 publications
(32 reference statements)
3
71
0
1
Order By: Relevance
“…It is also noteworthy that there are data to indicate that progestin-based contraceptives increase the susceptibility of a woman to develop gonococcal disease (13,32,36). I have now similarly shown that Pg, in a dose-dependent manner, augments the ability of gonococci to invade and to survive within pex cells.…”
Section: Discussionmentioning
confidence: 54%
“…It is also noteworthy that there are data to indicate that progestin-based contraceptives increase the susceptibility of a woman to develop gonococcal disease (13,32,36). I have now similarly shown that Pg, in a dose-dependent manner, augments the ability of gonococci to invade and to survive within pex cells.…”
Section: Discussionmentioning
confidence: 54%
“…16 DMPA usage has also been associated with increased acquisition of cervical chlamydial and gonococcal infections. 21 These STIs have also been linked to increased HIV-1 acquisition. Consistent with the clinical data, MPA increases susceptibility to vaginal simian-human immunodeficiency virus (SHIV) transmission and suppresses the antiviral cellular immune response in SHIV-infected rhesus macaques.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and epidemiological evidence suggests that the use of MPA as a contraceptive may increase the risk of acquiring genital tract infections such as herpes simplex virus type (HSV)-2 (17), Chlamydia (18), gonorrhea (19), and HIV-1 (6, 20 -22). The lower female genital tract is the primary site of exposure to the majority of these sexually transmitted pathogens (23)(24)(25)(26).…”
mentioning
confidence: 99%